Morus alba L. Cell Cultures as Sources of Antioxidant and Anti-Inflammatory Stilbenoids for Food Supplement Development - Vanessa Dalla Costa; Anna Piovan; Paola Brun; Raffaella Filippini (Molecules)
Morus alba L. (Moraceae), white mulberry, is an ancient, well-known source of several compounds with potent biological activities and beneficial effects on human health. In this study, the juices of three stabilised undifferentiated cell lines, calli maintained in light and dark conditions, and suspensions maintained in dark condition of M. alba were investigated for their phytochemical content and biological activity. The results highlighted the main presence of oxyresveratrol and resveratrol-backbone glucosides, together with benzofuran derivatives. Oxyresveratrol triglucoside was found for the first time in M. alba in vitro cultures, where it represents the main compound, accounting for almost 90 µg/mL in all the juices. The total stilbenoid content resulted significantly higher in calli juices during the logarithmic phase of the growth cycle, and cell suspension juice exhibited the statistically highest total content (313.21 µg/mL of juice). Only cell suspension juice showed ROS reduction in Caco-2 cells, whereas all the juices reduced IL-1β and TNF-α levels in Caco-2 cells stimulated with LPS. These results lay the groundwork for the future exploitation of M. alba dedifferentiated cultures as sustainable resources of stilbenoid compounds to be used in the nutraceutical, cosmetic, and pharmaceutical industries.